2008
DOI: 10.1248/bpb.31.1075
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Inducing Effects of Two Anthraquinones from Hedyotis diffusa WILLD.

Abstract: Two anthraquinones which inhibit activity of the Src tyrosine kinase were isolated from a water extract of Hedyotis diffusa WILLD. and identified as 2-hydroxy-3-methylanthraquinone (compound 1) and 1-methoxy-2-hydroxyanthraquinone (compound 2). Both compounds showed inhibitory activity against protein tyrosine kinases v-src and pp60src and arrested the growth of SPC-1-A, Bcap37 and HepG2 cancer cells. Observation of mitochondrial membrane potential collapse and caspase-3 activation following treatment with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…[5] HepG2 cells 2-Hydroxy-3-methyl anthraquinone 1-Methoxy-2-hydroxy anthraquinone Both compounds showed inhibitory activity against protein tyrosine kinases v-src and pp60src and arrested the growth of HepG2 cancer cells. [38] Bcap37 cells 2-Hydroxy-3-methyl anthraquinone, 1-Methoxy-2-hydroxy anthraquinone Both compounds showed inhibitory activity against protein tyrosine kinases v-src and pp60src and arrested the growth of Bcap37 cells. [38] Cervical tumor Nude mouse model Aqueous extract…”
Section: Ht-29 Cells Ethanol Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] HepG2 cells 2-Hydroxy-3-methyl anthraquinone 1-Methoxy-2-hydroxy anthraquinone Both compounds showed inhibitory activity against protein tyrosine kinases v-src and pp60src and arrested the growth of HepG2 cancer cells. [38] Bcap37 cells 2-Hydroxy-3-methyl anthraquinone, 1-Methoxy-2-hydroxy anthraquinone Both compounds showed inhibitory activity against protein tyrosine kinases v-src and pp60src and arrested the growth of Bcap37 cells. [38] Cervical tumor Nude mouse model Aqueous extract…”
Section: Ht-29 Cells Ethanol Extractmentioning
confidence: 99%
“…[38] Bcap37 cells 2-Hydroxy-3-methyl anthraquinone, 1-Methoxy-2-hydroxy anthraquinone Both compounds showed inhibitory activity against protein tyrosine kinases v-src and pp60src and arrested the growth of Bcap37 cells. [38] Cervical tumor Nude mouse model Aqueous extract…”
Section: Ht-29 Cells Ethanol Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…According to TCM, heat is considered an important causative factor in HCC, and Qingre Jiedu has been administered to clear heat and detoxify the body (6). Previous pharmacological studies have demonstrated that Qingre Jiedu herbs (including Hedyotis diffusa Willd, Prunella vulgaris, Lobelia chinensis Lour and Sophora flavescens) contain anthraquinones, polysaccharides, flavonoids, alkaloids and triterpenoids that are able to inhibit tumor cell proliferation, induce cell apoptosis and suppress angiogenesis (9)(10)(11). Matrine from Sophora flavescens is able to induce the apoptosis of HepG2 cells via the upregulation of tumor protein 53, B cell lymphoma-2 (Bcl-2)-associated X protein (Bax) and Fas, and the downregulation of Bcl-2 and c-Myc (12).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al (2011b) indicated that Hedyotis diffusa had an antiproliferative-activity on Murine leukemia WEHI-3 cells, and could promote T-and B-cell proliferation in leukemic mice. In addition, there were several further reports about the effect of Hedyotidis diffusae herba on different cancer cells (Chen et al, 2012;Gupta et al, 2004;Lee et al, 2011;Shi et al, 2008;Wang et al, 2011;Willimott et al, 2007). Due to the broad anticancer activity of Hedyotidis diffusae herba, its chemical components have drawn our attention.…”
Section: Introductionmentioning
confidence: 99%